Long-term adherence to adapted physical activity in patients with chronic inflammatory arthritis: Insights from a longitudinal observational study - Hugo Gondouin; Mathias Poussel; Eliane Albuisson; Margaux Temperelli; Oriane Hily; Anthony Moussu; Isabelle Chary-Valckenaere; Damien Loeuille; Bruno Chenuel; Edem Allado (PLoS ONE, 2026)
Adapted physical activity is recommended as a non-pharmacological strategy for the management of chronic inflammatory arthritis. However, the long-term adherence of patients to physical activity programs remains a major challenge in clinical practice. The present study aimed to assess adherence to World Health Organization (WHO) physical activity recommendations and to identify factors associated with long-term adherence in patients with chronic inflammatory arthritis (CIA). This longitudinal observational study included patients with spondyloarthritis, psoriatic arthritis, or rheumatoid arthritis who were referred to a specialized center for adapted physical activity between 2019 and 2021. Baseline demographic, clinical, and treatment-related variables were collected during the initial medical consultation. In August 2023, participants were contacted by telephone to assess their level of physical activity using a standardized questionnaire. Adherence was defined as meeting the WHO recommendations of at least 150 minutes of moderate-intensity physical activity or 75 minutes of vigorous physical activity per week. Among the 78 patients initially included, 61 responded to the follow-up assessment. Of these, 41 participants (67.2%) met the WHO physical activity recommendations. In univariate analyses, no clinical or treatment-related variables were significantly associated with long-term adherence. Male sex was the only factor significantly associated with adherence, with men showing a higher likelihood of meeting the WHO recommendations after adjustment for underlying pathology (OR 7.85, 95% CI 1.60–38.42). In this real-world cohort of patients with chronic inflammatory arthritis, approximately two-thirds of respondents maintained a level of physical activity consistent with WHO recommendations more than one year after the initial consultation. Clinical disease characteristics were not associated with adherence, while sex appeared to influence long-term engagement in physical activity. These findings highlight the need for further studies to better understand determinants of long-term adherence to adapted physical activity in this population.